PENGARUH CUSTOMER EXPERIENCE DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI PADA MARKETPLACE LOKAL DI LABUHA NBATU - Arya Syahputra; Muhammad Irwansyah Hasibuan (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the effect of customer experience and consumer trust on purchase intention in local marketplaces in Labuhanbatu. This research uses a quantitative approach with a survey method by distributing questionnaires to 150 respondents who are users of local marketplaces. The data analysis technique used is multiple linear regression analysis with the help of SPSS software. Before conducting the analysis, the data were tested using validity, reliability, and classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results showed that all statement items were valid and reliable. The classical assumption tests also indicated that the data were normally distributed and free from multicollinearity and heteroscedasticity problems. The results of the t-test showed that customer experience has a positive and significant effect on purchase intention with a regression coefficient of 0.498 and a significance value of 0.000. In addition, consumer trust also has a positive and significant effect on purchase intention with a regression coefficient of 0.421 and a significance value of 0.000. The F-test results indicate that customer experience and consumer trust simultaneously have a significant effect on purchase intention with an F value of 51.872 and a significance value of 0.000. The coefficient of determination (R Square) of 0.692 indicates that 69.2% of the variation in purchase intention can be explained by these independent variables, while the remaining is influenced by other variables outside this study. Thus, it can be concluded that improving customer experience and consumer trust are important factors in increasing purchase intention in local marketplaces.